ChemInform Abstract: Pb5Fe3TiO11Cl: A Rare Example of Ti(IV) in a Square Pyramidal Oxygen Coordination. Issue 31 (5th August 2014) - Batuk, Maria; Batuk, Dmitry; Abakumov, Artem M.; Hadermann, Joke
Abstract The title compound is prepared by solid state reaction of PbO, PbCl2, TiO2, and Fe2O3 (670 °C for 10 h and 800 °C for 20 h) and characterized by powder neutron and X‐ray diffraction, and high‐angle annular dark‐field STEM.